Reactivity of Monochlorotetrakis2-Isopropylphenoxoniobium(V), [NbCl(OC6H4CH(CH3)2-2)4] towards Chelating Ligands - Dr Mala Sharma* (International Journal of Minerals, 2026)
The niobium(V) complexes with the formula [NbCl(OC₆H₄CH(CH₃)₂-2)₄] were successfully synthesized in high yields through the reaction of niobium pentachloride with four equivalent amounts of 2-isopropylphenol in carbon tetrachloride. The synthesized complexes were characterized and confirmed by elemental analysis, molar conductance measurements, infrared (IR) spectroscopy, ^1H and ^13C NMR spectroscopy, as well as mass spectrometric analysis. The spectroscopic studies have shown these to exhibit dimeric structures bridging through isopropylphenoxo groups. The X-ray diffraction study of complexes has suggested their amorphous nature. The methanolic solution of newly synthesized complex monochlorotetrakis2-isopropylphenoxoniobium(v), [NbCl(OC6H4CH(CH3)2-2)4] react with equimolar amounts of chelating ligands such as β-Diketone, α-hydroxyketone and α-hydroxyaldehydes viz. Acetylacetone(acacH), Benzoin(benzH) and Salicylaldehyde(salH) (LH) in benzene to yield 1:1 coordination compounds authenticated by physicochemical, IR and 1H NMR spectral studies. The spectral data demonstrate that these chelating agents such as Acetylacetone(acacH), Benzoin(benzH) and Salicylaldehyde(salH), are effective in isopropylphenoxo bridging bond-scission and yield unimolecular compounds.
Keywords: Niobium(V) 2-isopropylphenoxide; chelating agents; coordination compounds; spectroscopic studies